1992
DOI: 10.1029/92jd02052
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of long‐period waves using the mesosphere‐stratosphere‐troposphere radar at Poker Flat, Alaska

Abstract: Using the mesosphere-stratosphere-troposphere radar at Poker Flat, Alaska, the long-period waves (greater than 1.5 but less than 36 days) in the troposphere/lower stratosphere and mesosphere were analyzed for the first 340 days of 1984. A 16-day wave was significant the whole year in all regions resolved by the radar and had maxima in the winter lower stratosphere, consistent with the (1,3) Rossby normal mode. Contrm'y to the theory of the (1,3) normal mode, the observed 16-day wave had a maximum in the summer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
116
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(131 citation statements)
references
References 21 publications
(5 reference statements)
13
116
2
Order By: Relevance
“…It has been confirmed that PWs extensively exist in the TLS, mesosphere and ionosphere (Hirota and Hirooka, 1984;Hirooka and Hirota, 1985;Randel 1987;Forbes and Leveroni, 1992;Williams and Avery, 1992;Tsuda et al, 1994a;Smith, 1997;Lawrence and Jarvis, 2003;Kishore et al, 2004), and contribute significantly to the variability of atmospheric parameters in these regions. Some literature (Tsuda et al, 1994a;Lawrence and Jarvis, 2003;Lu et al, 2005) has revealed that PWs in the TLS have significant wind amplitudes (>10 ms −1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been confirmed that PWs extensively exist in the TLS, mesosphere and ionosphere (Hirota and Hirooka, 1984;Hirooka and Hirota, 1985;Randel 1987;Forbes and Leveroni, 1992;Williams and Avery, 1992;Tsuda et al, 1994a;Smith, 1997;Lawrence and Jarvis, 2003;Kishore et al, 2004), and contribute significantly to the variability of atmospheric parameters in these regions. Some literature (Tsuda et al, 1994a;Lawrence and Jarvis, 2003;Lu et al, 2005) has revealed that PWs in the TLS have significant wind amplitudes (>10 ms −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some literature (Tsuda et al, 1994a;Lawrence and Jarvis, 2003;Lu et al, 2005) has revealed that PWs in the TLS have significant wind amplitudes (>10 ms −1 ). And, it was suggested that the PWs in the mesosphere and ionosphere were the result of upward propagating PWs in the TLS (Forbes and Leveroni, 1992;Williams and Avery, 1992;Smith, 1997). Therefore, the studies on PWs in the TLS deserve more efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Salby (1981a) suggested on theoretical grounds that the 16-and 5-day planetary waves are manifestations of the gravest symmetrical wavenumber 1, westward-travelling Rossby wave. The periods of the 16-and 5-day wave has, in fact, been observed to be between about 12-20 days and 4-7 day, respectively (e.g., Williams and Avery, 1992;Luo et al, 2000Luo et al, , 2002aLieberman et al, 2003;Riggin et al, 2006;Belova et al, 2008;Day and Mitchell, 2010a,b). The 16-day wave has been reported to have wind amplitudes of up to about ∼15 m s −1 and temperature amplitudes reaching…”
Section: K a Day Et Al: Mean Winds Temperatures And The 16-and 5-dmentioning
confidence: 99%
“…It has been shown that the interaction of tides with these waves modifies the amplitude of the tides significantly and also advances their phase [Hagan, 2000]. Some earlier studies have shown that the background wind reveals periodicities of 2-20 days in the 80-100 km regime [Manson and Meek, 1990;Williams and Avery, 1992;Miyoshi, 1999]. Recent studies have revealed that PWs at mesospheric heights are capable of interacting nonlinearly with the tides, modifying the tidal components significantly [Teitelbaum and Vial, 1991;Beard et al, 1999;Mitchell et al, 1999, and references therein].…”
Section: Resultsmentioning
confidence: 99%